Biscurcudiols, myrmekioperoxides, and myrmekiodermaral from the Thai marine sponge Myrmekioderma sp. Issue 19 (8th May 2020) - Wongbundit, Siriporn; Mahidol, Chulabhorn; Kaweetripob, Wirongrong; Prachyawarakorn, Vilailak; Eurtivong, Chatchakorn; Sahakitpichan, Poolsak; Tuntiwachwuttikul, Pittaya; Ruchirawat, Somsak; Prawat, Hunsa
Abstract: The chemical investigation of the Thai marine sponge Myrmekioderma sp. yielded three aromatic bisabolane dimers, ( R )- and ( S )-4, 6″-biscurcudiols (1 and 2 ) and myrmekiodermaral (5 ), and two bisabolane sesquiterpenes, myrmekioperoxides A (3 ) and B (4 ), along with seven known bisabolane sesquiterpenes (6 –12 ). All compounds were identified by extensive study of their spectral data, including HRAPCIMS or HRESIMS, 1D and 2D NMR data, as well as by comparison of their spectroscopic data with those reported in the literatures. The absolute configuration of compounds 1 and 2 were established on the basis of experimental and calculated ECD spectra and compared the 1 H NMR data with those of dicurcuphenols B and C. Ten of the isolated compounds were evaluated for cytotoxicity against a panel of cancer cell lines, including HuCCA-1, A549, HeLa, HepG2, MDA-MB-231, and MOLT-3. Graphical abstract: Image 1 Highlights: Three new dimer bisabolanes were isolated from the Thai sponge Myrmekioderma sp . Their structures were on the basis of NMR Spectroscopy and HRESIMS. Their structures provide chemotaxonomic evidence within the genus Myrmekioderma.